ANALYSIS OF THE EFFECT OF HSS TOOL ANGLE ON TOOL LIFE IN ST-37 STEEL MANUFACTURING. - Athallah, Helmi (Jurnal Energi Dan Manufaktur, 2023)
The turning process is one of the machining processes for producing machine components. Where the lathe process is included in the machining process that uses a chisel. The quality of the cut surface depends on the cutting conditions, for example a low cut with a large feed and depth of cut will result in a rough surface and so on. This study aims to determine what the effect of the angle on the length of use of the chisel, where the chisel used is an HSS chisel. In this study using experimental research methods with the aim of knowing the time difference obtained from the results of the different angles on the HSS chisel. The workpiece used is the type of ST-37 steel material. In this study, 3 chisel samples were made with different angles but still using the same rotational speed of 252 rpm. The workpiece feed is stable in other words using the same feed, which is 2mm. After performing the turning process using 3 different chisels, different time difference results will be obtained, then an analysis of what happens to the effect of the hss tool angle on the length of use of the chisel in the ST-37 material turning process. In this research, the results of the data show that the influence of the angle is very significant on the life of the tool.